Development of a sensitive and fast UHPLC–MS/MS method for determination of clopidogrel, clopidogrel acid and clopidogrel active metabolite H4 in human plasma. (July 2015) - Hua, Wenyi; Lesslie, Michael; Hoffman, Brian T; Binns, Christopher; Mulvana, Daniel
Background: Quantitation of CAM H4 in biological matrix has been a challenge due to low concentrations, instability and the existence of four CAM diastereomers. Historically, either inactive clopidogrel acid or CAM diastereomers without separation were measured for exposure and PK parameters.Results: This study presents a sensitive and fast UHPLC–MS/MS method for simultaneous quantitation of clopidogrel, clopidogrel acid and active metabolite H4 in human plasma. The method demonstrated the separation of H4 from other isomers and yet retained clopidogrel acid. Matrix stabilities, accuracy and precision, recovery and matrix effect were evaluated during development.Conclusion: With LLOQ of 0.05 ng/ml for clopidogrel and H4, and 5.5 min LC gradient, it is the most sensitive and fastest method to our knowledge.